The Mill on the Floss - Eliot, George (London, Penguin books, Ltd, 1994)
As Maggie Tulliver approaches maturity she enters into conflict with family and community over her desire for self-fulfillment. Eliot's exploration of Maggie's dilemma makes this novel as relevant today as it was in the 19th century